A novel decoupled parallel mechanism with two translational and one rotational degree of freedom and its performance indices analysis. (2nd May 2016) - Zeng, Daxing; Jing, Guoning; Su, Yonglin; Wang, Yi; Hou, Yulei
Less degrees of freedom parallel mechanism is widely used in many fields with its unique advantages. A decoupled parallel mechanism with 2 degree-of-freedom translation and 1 degree-of-freedom rotation is presented, and its performance evaluation indices analysis is performed. By the constraint screw method, the motion feature of the mechanism and its number of degree of freedom are analyzed. The constrained equations of the mechanism are established according to the constrained conditions of the pole length. The analytical expression of the forward and inverse position for the mechanism is deduced, and the expression of the Jacobian matrix is derived, which validated the decoupling feature of the mechanism. The singularity of the mechanism is also carried out. The performance evaluation indices for the decoupled parallel mechanism are discussed and the corresponding performance indices analysis of the proposed decoupled parallel mechanism is executed. The novel decoupled parallel mechanism presented herein enriches the parallel mechanism structure, and the definition and analysis of the performance evaluation indices should be meaningful for the further design and optimization of the decoupled parallel mechanism.